Life-cycle of structures and infrastructure systems : proceedings of the Eighth International Symposium on Life-Cycle Civil Engineering (IALCCE 2023), 2-6 July, 2023, Politecnico di Milano, Milan, Italy /: proceedings of the Eighth International Symposium on Life-Cycle Civil Engineering (IALCCE 2023), 2-6 July, 2023, Politecnico di Milano, Milan, Italy. (2023) - Unknown
No abstract available